Pengelolaan Keuangan Dana Desa (Desa Amahai, Kecamatan Amahai, Maluku Tengah) - Syahrina Noormala Dewi; Clara Oktavia Lernaya (Universitas PGRI Madiun, 2020)
The purpose of this study was to find out the management of village funds and the implementation of development in the field of empowerment of the Amahai village community, the central district of Amahai Maluku starting form the planning, implementation and administration stages. Data collection is done by observation, interviews and documentation. Data analysis model use reduction, data presentation and conclusion drawing.The results of the study show that the management of village funds in Amahai in the field of community empowerment at the planning, implementation and administration stages has been said to be good even though is has not been effective. This was evidenced by the preparation of the RPJM and RKP on time but out of thirteen community empowerment activities, eleven activities were realized and two activities were not realized.Key Words : Villages Funds, Empowerment Community